Dosis de humus de Lombriz (Eisenia foetida) y su respuesta en la producción de Biomasa y el rendimiento en el cultivo de Habitas (Phaseolus coccineus), en San Martín - Perú - Delgado Haya, Alamiro (2007)
The present work details the study • Doses Of Humus Of Earthworm And its Answer In The Production Of Biomass And The Performance In The Cultivation Of Habitas (Phaseolus coccineus) IN SAN MARTIN - PERU" where the objectives were quantify the fixing of C02, the production of biomass and the performance in the cultivation of habitats with 03 doses of fertilizing with humus of earthworm. In the same way realize the economic analyze of each one of the treatments. This work investigation was realize in the Miraflores fundo situated to 3.5 kilometers of Tarapoto sector the Banda of Shilcayo property of the National University of San Martín. The design experimental used in this work was of a design of blocks completly to chance with five treatment and tour repetitions. The parametos to evaluate were high of plant, number of pods, percentage of germination, performance and the production of biomass for each one of the treatments of which ones that had doses of humus of earthworm they gave the best results about production, number of pods, high of plants and production of biomass, in the same way it improve the texture, Ph, quantity of M.O of ground. According the relation benefit /cost I obtained a benefit in the second campaign still about of the cost of humus of earthworm in this 1 didn't applied it, obtained the treatment 3 (6 TM/ HL) with a benefit of 1428.84 S/. and the treatment 5 ( absolute) with a benefit of 348.92 SI. Respectively, assume that the power of residualidad of humus of earthworm is of a average of three years about of the investigations realized in others growings.